Summary Brief: Heifer study on climate-smart agriculture adoption rates amongst goat farming households in three districts of Nepal and the impact on key environmental and economic indicators - Giles, James Edward; Mwema, Emmanuel; Notenbaert, An Maria Omer; Caulfield, Mark E.; Otieno, Mary Atieno; Sheikh, Asjad Tariq; Poudel, Avash (2023)
This info brief provides an executive overview of the research methods and key finding of a series of information briefs. The briefs were developed to assess the role of Heifer Nepal programming in supporting the adoption of Climate-Smart Agriculture (CSA) practices amongst Heifer supported goat cooperatives, and their impact on a range of environmental and economic indicators. The recommendations of the analysis are intended to further strengthen the integration of climate change considerations into Heifer Nepal’s programming, with the goal of raising overall household incomes amongst supported households through means that have minimal negative impact on the environment. The research was conducted in three districts encompassing the main agro-ecological contexts in which Heifer Nepal works.